Hierarchical mesoporous yolk-shell structured carbonaceous nanospheres for high performance electrochemical capacitive energy storage - Yang, T.; Zhou, R.; Wang, D.; Jiang, San Ping; Yamauchi, Y.; Qiao, S.; Monteiro, M.; Liu, Jian (The Royal Society of Chemistry, 2015)
Hierarchical mesoporous yolk–shell structured carbon nanospheres (YSCNs) with an ordered mesoporous carbon core and a microporous carbon shell show excellent electrochemical performance with a maximal specific capacitance of 159 F g−1.